MBE growth, characterisation and physics of antiferromagnetic copper manganese arsenide - Hills, Victoria Anne (2016)
Research into antiferromagnetic materials for application in spintronics has rapidly expanded in recent years. The prediction and observation of spin based phenomena with antiferromagnets as the active components, has expanded the field and there is a need for high quality materials that are compatible with existing III-V semiconductor systems to expand this research. Copper manganese arsenide is one such material and will be the subject of this thesis. Early studies had shown that this material grows epitaxially on both gallium arsenide and gallium phosphide substrates by molecular beam epitaxy. This thesis builds on this early work by further characterising CuMnAs, improving the techniques used to grow it, and enhancing our understanding of the material. A key result of this thesis is that the Néel temperature of CuMnAs can be studied using temperature dependent transport measurements. This method allows for a range of layer thickness (from between 5 and 140 nm) to be studied. We find that the Néel temperature of CuMnAs is suppressed by around 100K when the layer thickness is less than 10nm. At the thicknesses studied there is agreement (around (480±5)K) with the more established neutron diffraction technique for measuring Néel temperature, which was also used to determine the magnetic structure of the CuMnAs studied. In addition to measurement of the Néel temperature of CuMnAs, a detailed study is made in this thesis of the ideal growth conditions for ultrathin (sub 10nm) films of CuMnAs. Post-growth examination of ultrathin layers of CuMnAs showed that significant portions of material were missing due to poor adhesion. This thesis shows the results of the development of several different nucleation and growth methods, which were used to improve the adhesion of the CuMnAs layer to the substrate. These methods are evaluated using atomic force microscopy, x-ray diffraction, magnetometry and transport measurements. CuMnAs has previously shown to strongly prefer growth under stoichiometric conditions, as non-stoichiometric conditions have tended to favour the formation of clusters of the excess material. In excess Mn conditions these clusters are ferromagnetic MnAs inclusions that are conducting and contribute to the magnetic behaviour. This thesis presents the results of a simulation study of the conductivity of ferromagnetic elements in a non-ferromagnetic medium. This approach could be extended to allow the number of inclusions in a CuMnAsl layer to be approximated from transport measurements. Finally, this thesis will also look at the effects of alloying CuMnAs with phosphorous. This reduces the lattice constants of the material while retaining the same crystal and magnetic structure. In thick films of the alloy the Néel temperature increases from that of CuMnAs.